2015
DOI: 10.1016/j.jcis.2015.07.051
|View full text |Cite
|
Sign up to set email alerts
|

The drainage of foamy granular suspensions

Abstract: Foam-based materials are promising micro-structured materials with interesting thermal and acoustical properties. The control of the material morphology requires counteracting all the destabilizing mechanisms during their production, starting with the drainage process, which remains to be understood in the case of the complex fluids that are commonly used to be foamed. Here we perform measurements for the drainage velocity of aqueous foams made with granular suspensions of hydrophilic monodisperse particles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 24 publications
1
42
1
Order By: Relevance
“…The modeling of the mechanical consequences of such a morphological evolution is challenging, and this aspect would certainly deserve a dedicated work. Here, we refer to a previous work [23] dealing with the drainage of foamy granular suspensions. At first sight, there is no direct comparison between foam drainage and the foam mechanics but, as we will show in the following, those two issues involve the same morphological transition.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The modeling of the mechanical consequences of such a morphological evolution is challenging, and this aspect would certainly deserve a dedicated work. Here, we refer to a previous work [23] dealing with the drainage of foamy granular suspensions. At first sight, there is no direct comparison between foam drainage and the foam mechanics but, as we will show in the following, those two issues involve the same morphological transition.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Indeed, in [23] the viscous drag (resistance) experienced by the draining liquid was measured to be maximal (ܴ ௫ ) when trapped particles were fully included in the foam network, i.e. ߣ ≈ 1, but minimal (ܴ ) when the particles were fully excluded from the network, i.e.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Such a behavior can be explained by the effect of initial particle concentration on drainage [19]. For high concentration, particles are trapped by collective jamming, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, several foam aging processes act before the complete hardening of foamy systems to damage the microstructure that has been set up during the aeration step: the drainage of the interstitial phase (the continuous phase between the gas bubbles) and the simultaneous rising of the bubbles, the ripening (the gas exchange between bubbles) and the coalescence process [6,7]. Recent studies have shown that those aging processes can be controlled in taking advantage of the rheological properties of fluids to be foamed, such as clays [8,9], coal fly ashes [10], colloidal suspensions [11][12][13][14], emulsions [15][16][17], granular suspensions [18,19]. In the elaboration of optimized foamed materials, the rheological behavior of those complex foams is also of primary interest.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on foams made with complex fluids such as concentrated emulsions 5,6 , polymer gels [7][8][9][10] or particle suspensions such as clays [11][12][13][14] , granular suspensions 15,16 , surfactant/particle suspensions 12,13,[17][18][19][20][21][22] . When particles or particle aggregates are large enough, they accumulate in the Plateau borders of the foams and help slowing down the drainage of the foams 15,16,23 . When the particle suspensions exhibit a finite yield stress, this may lead to a complete arrest of the drainage flow 17,24,25 .…”
Section: Introductionmentioning
confidence: 99%